One small square seashore - Silver, Donald M., 1947-; Wynne, Patricia (New York : Scientific American Books for Young Readers, 1993)
Examines small portions of a sandy East Coast beach and a rocky West Coast shore and describes the life they support.
13
Keywords: Intertidal ecology -- Juvenile literature; Seashore ecology -- Juvenile literature; Ecology